Influence of the AOT counterion chemical structure in the generation of organized systems - Lépori, Cristian Marcelo Oscar (2020)
The impact of the imidazolium counterion structure on the organized systems formed by the surfactant 1,4-bis-2-ethylhexylsulfosuccinate, AOT, both in aqueous solutions and in nonpolar solvents is investigated. With this in mind, we investigated if the ionic liquid-like (IL-like) surfactant 1-ethyl-3-methylimidazolium 1,4-bis-2-ethylhexylsulfosuccinate, emim-AOT, forms direct micelles or vesicles in water. Dynamic light scattering, zeta potential, conductivity, fluorescence spectroscopy, and UV-visible spectroscopy measurements were performed to characterize the organized systems in aqueous solutions. We also studied the self-aggregation of emim-AOT, 1-butyl-3-methylimidazolium 1,4-bis-2-ethylhexylsulfosuccinate, bmim-AOT, and of 1-hexyl-3-methylimidazolium 1,4-bis-2-ethylhexylsulfosuccinate, hmim-AOT, in nonpolar solvents. The results obtained showed that the IL-like surfactant emim-AOT forms direct micelles in water, as sodium 1,4-bis-2-ethylhexylsulfosuccinate (Na-AOT) does. However, emim-AOT aggregates are larger, have a lower surface charge, are more stable, and have a more polar and less fluid micellar interface than Na-AOT micelles. It was also observed that emim-AOT and hmim-AOT form reverse micelles in nonpolar solvents. The size of the imidazolium cations dramatically influences the size of the reverse micelles and their ability to solubilize water.